Non-face-to-face physical activity interventions in older adults: a systematic review - Müller, A.M. (BioMed Central, 2014)
Physical activity is effective in preventing chronic diseases, increasing quality of life and promoting general health in older adults, but most older adults are not sufficiently active to gain those benefits. A novel and economically viable way to promote physical activity in older adults is through non-face-to-face interventions. These are conducted with reduced or no in-person interaction between intervention provider and program participants. The aim of this review was to summarize the scientific literature on non-face-to-face physical activity interventions targeting healthy, community dwelling older adults (≥ 50 years). A systematic search in six databases was conducted by combining multiple key words of the three main search categories ``physical activity'', ``media'' and ``older adults''.The search was restricted to English language articles published between 1st January 2000 and 31st May 2013. Reference lists of relevant articles were screened for additional publications. Seventeen articles describing sixteen non-face-to-face physical activity interventions were included in the review. All studies were conducted in developed countries, and eleven were randomized controlled trials. Sample size ranged from 31 to 2503 participants, and 13 studies included 60% or more women. Interventions were most frequently delivered via print materials and phone (n = 11), compared to internet (n = 3) and other media (n = 2). Every intervention was theoretically framed with the Social Cognitive Theory (n = 10) and the Transtheoretical Model of Behavior Change (n = 6) applied mostly. Individual tailoring was reported in 15 studies. Physical activity levels were self-assessed in all studies. Fourteen studies reported significant increase in physical activity. Eight out of nine studies conducted post-intervention follow-up analysis found that physical activity was maintained over a longer time. In the six studies where intervention dose was assessed the results varied considerably. One study reported that 98% of the sample read the respective intervention newsletters, whereas another study found that only 4% of its participants visited the intervention website more than once. From this review, non-face-to-face physical activity interventions effectively promote physical activity in older adults. Future research should target diverse older adult populations in multiple regions while also exploring the potential of emerging technologies.